Crosslinking of the acrylic pressure-sensitive adhesives using polycarbodiimides - Czech, Z. (Polimery, 2022)
The crosslinking of polyacrylic pressure-sensitive adhesives (PSAs) is an interesting method of modification of their physicochemical and mechanical properties. The syntheses and crosslinking of polyacrylic PSA, used for the manufacturing of pressure-sensitive protective films, have become recently of aspecial importance. In the paper the basic properties of polyacrylic PSA crosslinked with polycarbodiimides, such as tack, adhesion and cohesion, were determined. The tack was measured at temp. 20 °C while the other properties mentioned were determined at 20 and 70 °C. Taking into account the obtained values of tack, adhesion and cohesion one can find that the adhesives investigated are useful for the production of a wide variety of pressure-sensitive protective films.